2004
DOI: 10.1007/s00535-003-1241-5
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal pancreatic imaging in Crohn?s disease: prevalence and clinical features

Abstract: It is suggested that abnormal pancreatic imaging is not serious a complication of Crohn's disease, and is unrelated to the course of Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…10 In the present study, the frequency of AIP in CD patients was 0.4% and that of CD in definite AIP patients was 6.5% (2/31; unpublished data). 7,10,23,25-30 The prevalence (0.8%) of AIP in CD patients has seldom been reported.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…10 In the present study, the frequency of AIP in CD patients was 0.4% and that of CD in definite AIP patients was 6.5% (2/31; unpublished data). 7,10,23,25-30 The prevalence (0.8%) of AIP in CD patients has seldom been reported.…”
Section: Discussionsupporting
confidence: 50%
“…3 Type 2 AIP is characterized by a distinct pathology called idiopathic duct-centric pancreatitis (IDCP) 4 or AIP with granulocyte epithelial lesion (GEL). 10 We have retrospectively maintained a database of 7 patients with AIP and IBD in our institution. 6-9 However, far less is known about the clinical spectrum of AIP in Japanese patients with IBD.…”
mentioning
confidence: 99%
“…Patient #7, deceased at 37 y, had no children but had never been investigated for infertility. He had severe Crohn's disease and, though recurrent acute pancreatitis has been described in the course of this disease (Weber et al, 1993;Levine and Lukawski-Trubish, 1995;Oishi et al, 2004), the chronic pancreatitis in this patient may, in part at least, have been caused by alcoholism. 22; 23; 10-9; 7; 17 The recommendations for mutation nomenclature (www.hgvs.org/mutnomen/) were used to name CFTR gene sequence variations at the protein level.…”
mentioning
confidence: 99%
“…It has been suggested that pancreatitis could be an extrahepatic manifestation of inflammatory bowel disease, since its incidence in this disease is greater than that in the general population and in many cases no aetiological factor has been found [ 5 ]. It has been recently identified in Japan that over 6% of Crohn's disease patients had morphological abnormalities of the pancreas [ 6 ]. There is also a notion that Crohn's-associated pancreatitis could be a premalignant state for cystadenocarcinoma of the pancreas [ 7 ].…”
mentioning
confidence: 99%